PERLINDUNGAN HUKUM TERHADAP RAHASIA DAGANG - Syahriyah Semaun (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2011)
The secret of trade now is already one form of investment expensively beside the form of another investment that must be maintained against all parties for not abuse for interest of another parties through one mechanism of inhonest competition. The secret of trade is information in field of technology and business that is not known by public, to have value of economy caused by useful in activity of business, and kept the secret by the owner of the Trade Secret. The protection of law for secret of trade can be separated into some parts, they are: 1. There is contract element/agreement 2. The right of owner of Trade Secret is noticed (there is right of exclusive) 3. Display of unlawfull actions 4. The solution of conflict in state court 5. The transfer of rights of trade secret 6. There is no time period of protecting trade secret.What is the attempt of trade secret owner in maintaining the existence of trade secret for solving the competition that is not healthy by competitors and there is no good intention, and what is the form of conflict solution in breaking of the trade secret. System of Trade Secret Protection has wider scope, because there is provision in it that the breaker can be claimed by civil and criminal matter. The giving of law protection on trade secret has important meaning, namely as foundation for effective protection for forms of information secretly categorized as secret of the trade by regulation of preventing unhealthy practice of competition that can damage the people. It is suggested the protection of Law for Trade Secret is stipulated in better focus because Secret of trade is asset or investment with high value and expensive of price for person or organization as inventor of the Trade Secret, therefore government makes law regulation to regulate the things needed particularly in protecting an asset of high economic value such as Secret of Trade.